Intercultural skills : for international business and international relations: a manual with exercises - Verluyten, Sylvain Paul Marcel, ....- (Leuven : Acco, 2018)
This introduction to intercultural communication in international business, international relations and other situations of cross-cultural contact features the following unique highlights: ? It is rooted in history and anthropology, allowing the reader to situate intercultural issues in a wider humanistic framework. ? It offers practical advice that will be directly helpful in concrete intercultural settings. ? It goes through great lengths to warn against oversimplification and stereotyping, traps that are inherent in several publications in the field of intercultural publications. ? It is critical: it does not shy away from critically discussing various theories and statements that are found in the literature in order to arrive at a balanced view of what we can learn from research in the field. ? It encourages an open discussion of ethical issues related to multiculturalism and intercultural contact, also in the exercise section. ? It includes a substantial set of exercises of various types which will allow the reader to develop their intercultural skills. ? It blends into an online learning platform. ? It makes a set of pedagogical aids available to instructors.
Keywords: Go international; International relations